Coverage evaluation of primary immunization and the associated determinants in an urban slum of Rewa - Trivedi, Rohit; Singh, Sandeep; Adhikari, Paharam; Jatav, Durga Prasad (Indian Journal of Community Health, 2014)
Back ground: - Immunization coverage has been found to be low in many coverage evaluation studies done in India, especially among the marginalized community. Aim:-To find the primary immunization coverage among the 12-23 months children and the determinants for the present status of immunization in an urban slum in Rewa city. Method - The study included 210 children in the age group of 12-23 months in an identified slum. The tools used were the WHO immunization evaluation coverage survey format and a pretested semi-structured schedule. Immunization card data and recall of mother or the primary caregiver was considered for assessing immunization status. Result: - Of all the children covered, 72.4 % were fully immunized and 21.9 % were partially immunized and 5.7% were not immunized. The commonest reason for incomplete immunization / partial immunization was found to be Lack of knowledge of immunization schedule to the parents 93.5%.Mother’s literacy and birth order of child were found to be more importantly associated with the status of child’s immunization. Conclusion:-Our observations reemphasized the need for adequate and proper counseling of parents on their children’s immunization.